Tuberculous ileo-colitis in Ibadan: a clinico-radiological review. Issue 8 (August 1972) - Lewis, E. A.; Kolawole, T. M.
Abstract : Twenty cases of tuberculous ileo-colitis with radiographic changes seen in the University College Hospital, Ibadan, Nigeria, are reviewed and the clinical features and radiographic patterns examined. The intestinal lesions in all cases were secondary to healed and active pulmonary tuberculosis. Although the ileo-caecal region is the commonest site of involvement, lesions also occurred in the distal part of the colon and the entire colon was sometimes involved. Rare occurrences, such as the diverticular type, enterolithiasis, tuberculosis presenting as intussusception and as an appendicular mass, are also reported. Four principal radiological types of colonic change emerged from the study, namely, the hyperplastic, the ulcerative, the mixed ulcero-hyperplastic, and the carcinoma-like types. The salient features in the differential diagnosis of ileo-colonic lesions in a tropical setting are discussed.